Asset productivity at container terminals in Latin America and the Caribbean: 2005-2013 - Doerr, Octavio (ECLAC, 2015)
This issue of the FAL Bulletin shows productivity trends at container terminals in Latin America and the Caribbean during the period from 2005 to 2013, comparing them to the trend of earlier years (2000 to 2004). One of the conclusions of the study is that most terminals in the region have improved their quay productivity in recent years, although there are large differences between the three container terminal size categories analysed. However, the author identifies a number of challenges still to be met at the region’s ports.